ANALISIS FAKTOR INTERNAL DAN FAKTOR EKSTERNAL YANG MEMPENGARUHI PROFITABILITAS PERBANKAN SYARIAH SEBELUM DAN SELAMA PANDEMI COVID-19 - Rizqa Tri Wulandari; Agung Juliarto (Diponegoro Journal of Accounting, 2023)
This study aims to examine the influence of internal factors and external factors on the profitability of Islamic banking and the impact of the Covid-19 pandemic on the influence of internal factors and external factors on the profitability of Islamic banking. There are seven independent variables in this study which consist of internal factors (company size, Capital Adequacy Ratio, Non-Performing Financing, Net Operating Margin, Financing to Deposit Ratio) and external factors (BI Rate and inflation). While the dependent variable in this study is Return on Assets (ROA).This research is a quantitative research. The population in this study is Islamic banking with a sample of Islamic Commercial Banks registered with the Financial Services Authority in the 2018-2021 period. Sampling was carried out by purposive sampling method. The data analysis technique used in this study is multiple linear regression analysis and the Chow test using the SPSS 25 application.The research results related to internal factors, only company size, NOM, and NPF variables have proven to have an effect on Islamic banking ROA. Of the two external factors which include the BI Rate and Inflation, none have proven to have an effect on the ROA of Islamic banking. In addition, this study did not find any differences in the influence of internal factors and external factors on Islamic banking ROA between before and during the Covid-19 pandemic.